The Effect on the Durability Properties of Concrete of Partial Replacement of Natural Fine Aggregates with Recycled Concrete Fine Aggregates - Kahabi, Neema (Department of Civil Engineering, 2023)
Rapid urbanization and advancement in concrete technology in the world has led to excessive exploitation of natural sand resources for use in the construction industry. This excessive utilization has led to the depletion of natural sand resources; for instance, in countries such as India and Indonesia, sand mafia and destruction of beaches due to illegal sand mining have been reported. These trends have forced the construction industry to adopt the use of alternative construction materials such as recycled aggregates into new construction as a measure to deal with this growing challenge. Currently, in South Africa, a blend of different types of sand is used for construction purposes due to variations in the sand quality and over exploitation of nearby deposits of natural sand resources. However, the adoption of recycled fine aggregates has been a challenge due to properties such as higher water absorption and lower relative densities of the aggregates along with the variation of material sources which attributes to the lower durability performance of concrete made with recycled fine aggregates. Durability of concrete with recycled fine aggregates is largely affected by the transport mechanisms which is influenced by the presence of residual mortar on the surface of recycled fine aggregates. This research involves an investigation on both mechanical properties such as compressive strength as well as durability properties such as resistance to penetration of aggressive ions, of concrete made with partial replacement of recycled fine aggregates.